2018
DOI: 10.1111/cea.13257
|View full text |Cite
|
Sign up to set email alerts
|

Changes in airway inflammation and remodelling in swimmers after quitting sport competition

Abstract: Intense swimming training in chlorinated pools affects the structure of the airways in elite swimmers. 1 Regardless of the magnitude of airway responsiveness, airway inflammation and remodelling are similar to those of non-athletes with mild asthma. Airway structural changes in swimmers are mainly characterized by increased mast cell and eosinophil numbers, collagen deposition and sub-epithelial basement membrane thickness. 1 A partial reversibility of airway hyperresponsiveness (AHR) has been reported in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In biopsies taken from six swimmers before and 2 years after retirement, collagen III expression was higher in retirement than during swim training and tenascin expression was unchanged after retirement. In the same study, lymphocytes and neutrophils were significantly reduced in all swimmers after retirement suggesting reversibility of bronchial inflammation that was present during a swim career (Bougault et al, 2018). The application of OCT imaging used in conjunction with our semi‐automated software can be used to address whether airway remodelling in elite athletes is reversible.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In biopsies taken from six swimmers before and 2 years after retirement, collagen III expression was higher in retirement than during swim training and tenascin expression was unchanged after retirement. In the same study, lymphocytes and neutrophils were significantly reduced in all swimmers after retirement suggesting reversibility of bronchial inflammation that was present during a swim career (Bougault et al, 2018). The application of OCT imaging used in conjunction with our semi‐automated software can be used to address whether airway remodelling in elite athletes is reversible.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, biopsy data from the segmental, subsegmental, and lobar airways have shown increased tenascin deposition and submucosal type I and type III collagen expression in elite swimmers compared to controls (Bougault et al, 2012). Whether or not the remodelling of airways in athletes is reversible upon cessation of competitive training is unclear (Bougault et al, 2018; Vergès et al, 2004). Evidence of deviations from normal healthy structure cannot be provided with certainty without quantitative analysis of airway structural components (Fehrenbach et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Discontinuation of a swimming career decreases eosinophilic and neutrophilic inflammation and reduces BHR, although these findings should be interpreted with caution given the small sample sizes. 71,72 These inflammatory changes did not seem, however, to correlate with BHR. A study carried out in a mixed population of competitive athletes including mostly non-asthmatic swimmers and speed skaters indicated that the baseline pattern of pro-inflammatory cytokine TNFα and antiinflammatory IL-1ra concentrations in the lower airways appears to be similar in top level athletes and asthmatic patients, but different in healthy controls.…”
Section: Work-related Exposurementioning
confidence: 78%
“…Inflammatory and remodeling changes reported in bronchial biopsies of competitive swimmers were similar to non‐exercising mild asthmatics and were present also during off‐training period. Discontinuation of a swimming career decreases eosinophilic and neutrophilic inflammation and reduces BHR, although these findings should be interpreted with caution given the small sample sizes 71,72 . These inflammatory changes did not seem, however, to correlate with BHR.…”
Section: Effects Of Chronic Exposuresmentioning
confidence: 79%
“…Inflammatory and remodeling changes reported in bronchial biopsies of competitive swimmers were similar to non-exercising mild asthmatics and were present also during off-training period. Discontinuation of a swimming career decreases eosinophilic and neutrophilic inflammation and reduces BHR, although these findings should be interpreted with caution given the small sample sizes 40,41 . These inflammatory changes did not seem, however, to correlate with BHR.…”
Section: Respiratory Symptomsmentioning
confidence: 92%